History of the Afghan Central Bank, its Sharīʿah supervision system and its effect on unifying the Sharīʿah reference - Athari, Zaif Ullah; Amanullah, Muhammad; Ghalia, Bouhedda (IIUM Press, 2024)
This article aims to explore the topic of Sharīʿah supervision in the Afghan Central Bank and its impact on unifying Sharīʿah reference. This is achieved through investigating the historical roots of banking activities, the establishment of the Afghan Central Bank, its Shari`ah supervision system, and its influence on unifying Sharīʿah reference in Islamic banks. The focus of this article will be on elucidating the establishment of the Afghan Central Bank and the opening of the field of financial transactions within its framework through rules and regulations. The current study also emphasizes the clarification of the supervisory role of the Central Bank in achieving the unification of Sharīʿah reference in Islamic banks. Researchers adopt a textual study approach, encompassing both inductive and analytical-critical methods to study scholars’ opinions on the subject and discuss them. Additionally, the researchers rely on field study methodology, conducting personal interviews with experts and specialists in the field. The current study reveals that the establishment of the Afghan Central Bank dates back to 1939 within a detailed historical context of banks in Afghanistan. Researchers also find that the Afghan Central Bank has a specific supervisory system for Islamic banks, playing a significant role in unifying Sharīʿah reference in these banks. However, it appears that there is no specific framework to regulate this aspect, in addition to the absence of truly independent Islamic government banks. Instead, there is a private Islamic bank and Islamic windows providing Islamic banking services under the supervision of the Afghan Central Bank. Nevertheless, the study notes several observations, including the absence of a specific and independent law for Islamic financial services in Afghanistan that regulates the activities of Islamic banks.